giant lens, a gene involved in cell determination and axon guidance in the visual system of Drosophila melanogaster. - Kretzschmar, D.; Brunner, A.; Wiersdorff, V.; Pflugfelder, G.O.; Heisenberg, M.; Schneuwly, S. (The EMBO Journal, 1992)
Mutations in the Drosophila gene giant lens (gil) affect ommatidial development, photoreceptor axon guidance and optic lobe development. We have cloned the gene using an enhancer trap line. Molecular analysis of gil suggests that it encodes a secreted protein with an epidermal-growth-factor-like motif. We have generated mutations at the gil locus by imprecise excision of the enhancer trap P-element. In the absence of gil, additional photoreceptors develop at the expense of pigment cells, suggesting an involvement of gil in cell determination during eye development. In addition, gil mutants show drastic effects on photoreceptor axon guidance and optic lobe development. In wildtype flies, photoreceptor axons grow from the eye disc through the optic stalk into the larval brain hemisphere, where retinal innervation is required for the normal development of the lamina and distal medulla. The projection pattern of these axons in the developing lamina and medulla is highly regular and reproducible. In gil, photoreceptor axons enter the larval brain but fail to establish proper connections in the lamina or medulla. We propose that gil encodes a new type of signalling molecule involved in the process of axon pathfinding and cell determination in the visual system of Drosophila.